THU0324 Disease activity and patient characteristics by comorbidity among psoriatic arthritis (PSA) patients in a us registry. (12th June 2018) - Mease, P.J.; Litman, H.J.; Accortt, N.A.; Rebello, S.; Greenberg, J.D.; Feng, H.; Gharaibeh, M.M.; Aras, G.A.; Collier, D.H.
Abstract : Background: PsA patients have greater prevalence of cardiovascular disease (CVD), metabolic syndrome (MetS), and cancer than patients without PsA. Objectives: To examine patient characteristics and disease activity by comorbidity profile among PsA patients. Methods: This analysis included adults with PsA enrolled in the US Corrona PsA/spondyloarthritis Registry from March 2013-March 2017 and followed for ≥6 months. Prevalence (at registry entry) and incidence rate (time to new events after registry entry) of CVD, MetS, and cancer were determined. Patient characteristics and disease activity were described by prevalent comorbidity, with t-tests for means despite skewed data and chi-squared tests for percentages. Results: The analysis included 1493 patients and 3564 patient-years of follow-up. Incidences (95% confidence interval) per 1000 patient-years were 9.4 (6.5–13.5), 1.0 (0.3–3.1), and 11.4 (8.2–15.8) for CVD, MetS, and cancer (6.8 [4.5–10.2] nonmelanoma skin cancer), respectively. PsA patients with (vs without) prevalent CVD, MetS, or cancer were older, and fewer had full-time jobs or private insurance. Patients with (vs without) CVD had higher swollen joint count and mean body surface area, and tended to have higher rates of obesity. Patients with (vs without) MetS tended to have greater disease activity. Patients with (vs without) comorbidities reported less disease activity on patient global assessment. Data are mean or% a ≥3 of 4 conditions: hypertension, hyperlipidemia, diabetes mellitus, or obesity b P value across all categories for employment or body mass index Conclusions: PsA patients with (vs without) CVD had greater disease activity and those with (vs without) MetS tended to have greater disease activity by physician-derived measures, but PsA patients with (vs without) CVD or MetS reported lower global assessment of disease activity. Patient perception of PsA may mask the effect of comorbid CVD or MetS on disease activity. Acknowledgements: Amgen Inc. supported this work. Corrona has been supported by AbbVie, Amgen, AstraZeneca, Boehringer Ingelheim, BMS, Crescendo, Eli Lilly and Company, Genentech, GSK, Horizon Pharma USA, Janssen, Momenta Pharmaceuticals, Novartis, Pfizer, Roche, and UCB. Jonathan Latham (PharmaScribe) and Linda Rice (Amgen) provided medical writing support. Disclosure of Interest: P. Mease Grant/research support from: Abbvie, Amgen, Bristol Myers Squibb, Janssen, Lilly, Novartis, Pfizer, Sun, UCB, Consultant for: Abbvie, Amgen, Bristol Myers Squibb, Janssen, Lilly, Merck, Novartis, Pfizer, Sun, UCB, Zynerba, Speakers bureau: Abbvie, Amgen, Bristol Myers Squibb, Genentech, Janssen, Novartis, Pfizer, UCB, H. Litman Employee of: Corrona, LLC, N. Accortt Shareholder of: Amgen Inc., Employee of: Amgen Inc., S. Rebello Employee of: Corrona, LLC, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: Genentech, Janssen, Pfizer, Eli Lilly, Novartis, Employee of: Corrona, LLC, H. Feng Employee of: Corrona, LLC, M. Gharaibeh Shareholder of: Amgen Inc., Employee of: Amgen Inc., G. Aras Shareholder of: Amgen Inc., Employee of: Amgen Inc., D. Collier Shareholder of: Amgen Inc., Employee of: Amgen Inc.